2004
DOI: 10.1590/s0103-50532004000300009
|View full text |Cite
|
Sign up to set email alerts
|

Mixed solid device based on conducting polymer composite and polymer electrolyte

Abstract: Filmes porosos de sílica sol-gel obtidos a partir de tetraetil ortosilicato (TEOS) foram utilizados como moldes para a polimerização eletroquímica da anilina. Foi investigado o comportamento redox e as capacidades de carga/descarga de uma bateria polimérica de lítio constituída pelo compósito polianilina-sílica, utilizado como catodo, e pelo eletrólito gel polimérico poli(dimetilsiloxano-coóxido de etileno). O compósito apresentou uma elevada capacidade inicial (140 mA h g -1 ) e uma capacidade reversível de 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
(21 reference statements)
0
9
0
Order By: Relevance
“…Polyaniline has been studied extensively as a supercapacitor or battery electrode material [11,15,19,27,42,44,49,50,53,[55][56][57][58][59][60][61][62][63][64][65][66][67][68]. The structure of polyaniline is illustrated in Fig.…”
Section: Polyanilinementioning
confidence: 99%
“…Polyaniline has been studied extensively as a supercapacitor or battery electrode material [11,15,19,27,42,44,49,50,53,[55][56][57][58][59][60][61][62][63][64][65][66][67][68]. The structure of polyaniline is illustrated in Fig.…”
Section: Polyanilinementioning
confidence: 99%
“…Polyaniline (PAn) is one of the most promising conducting polymer which has been frequently used as a low-cost positive electrode material for ES application due to its variable oxidation state, and excellent doping-dedoping characteristic, which contributes to a very high specific pseudocapacitance [68,95,[118][119][120][121][122][123][124][125][126][127][128][129]. Although the protonated emeraldine form of polyaniline has reported to have very poor conductivity, it is one of the most studied CPs due to its high doping level and environmental stability [68,130].…”
Section: Polyanilinementioning
confidence: 99%
“…This showed photoelectric behavior, where the conductivity of the polymer increased when supported with cellulose membrane, although the complete mechanism of this behavior was not entirely understood. [73,74] To demonstrate the applicability of cellulose as a smart electro-active material, a bending actuator was processed, fabricated and tested using cellulose paper by Kim et al [75] The concept of electroactive papers is demonstrated in Figure 3, which shows the cellulose electroactive paper as a bending actuator. Gold electrodes were deposited on both sides of the cellophane by means of physical vapor deposition.…”
Section: Conducting Compositesmentioning
confidence: 99%
“…Composite films, demonstrating acceptable conductivity, were obtained by the electropolymerization of aniline on a platinum electrode coated with a microporous cellulose acetate membrane. This showed photoelectric behavior, where the conductivity of the polymer increased when supported with cellulose membrane, although the complete mechanism of this behavior was not entirely understood 73, 74. To demonstrate the applicability of cellulose as a smart electro‐active material, a bending actuator was processed, fabricated and tested using cellulose paper by Kim et al75 The concept of electroactive papers is demonstrated in Figure 3, which shows the cellulose electroactive paper as a bending actuator.…”
Section: Applications Of Natural Fiber Reinforced Compositesmentioning
confidence: 99%